Peningkatan Kinerja Perusahaan Melalui Pelatihan Manajemen Logistik - Kusrini, Elisa; Annisa, Putri Dwi; Nailie Azzat, Noor; Munang, Aswan (Universitas Islam Indonesia, 2024)
Increasing logistics efficiency is one aspect that contributes to improving company performance through reducing costs, on-time delivery, and improving customer service. One effort to increase logistics efficiency is to increase the understanding of logistics actors themselves through training activities. Therefore, training activities are carried out from academics to logistics practitioners at companies operating in the logistics and supply chain sector. This training was carried out to increase knowledge and understanding of managing logistics. The training was conducted online and attended by various agency participants. The training material discusses efficiency strategies in logistics management and standardization of logistics performance. Various strategies in planning distribution and transportation, selecting transportation modes, selecting delivery routes, and the rules in Incoterm 2020 are discussed accompanied by examples and best practices. Based on the assessment of 14 participants, the pre-test results show that 50% of participants still got a score below 60 and the post-test score shows that the participants' knowledge has experienced a significant increase with more than 70% of participants getting a score above 80. This reflects an increase in understanding. from participants and demonstrate the effectiveness of the training. Collaboration between the world of practitioners and the world of academia needs to be improved, in the form of training programs for academics so that they can work together to contribute to the development of knowledge and increase professionalism in work to support progress and efficiency in various industrial sectors, especially in the fields of logistics and supply chain.